Male Perception of Female Participation and VAW on the Virtual Learning App – “Hallo” - Aziza Hena (The Journal of Society and Media, 2022)
This study explored men's perception of women's participation and VAW (Violence against women) on an online learning platform called "Hallo." Based on the analysis of in-depth interviewed data collected from male users of the application, the study found that men hold an egalitarian view in respect of the participation of their female counterparts. Though most men perceived the platform as a tool for women's empowerment through educative elements, exchange of knowledge, language learning opportunities, and development of communication skills, they did not fail to give proper attention to women's safety on this digital podium. Emphasis was given to women's 'self-responsibility' and 'awareness' to handle violence perpetrated by male users against them. Primarily, cultural and religious boundaries, strengthened by patriarchy, were marked as leading determiners of women's communication leeway in the learning space. Besides that, the normalization of violence was found justified by divergent labels such as 'mere amusement,' 'right to freedom of expression,' or 'temporary moral shift.' Moreover, the study discovered that women of Asian and Arab origins get victimized specifically for their stereotypical feminine temperament. At the same time, rude talking patterns, fame motives, or dating intentions are considered liable for violence against women regardless of their race, color, creed, or location.